Do not go gentle : my search for miracles in a cynical time - Hood, Ann, 1956- (New York : Picador USA, 2000)
Ann Hood was firmly rooted in the physical world-- practical, realistic, and skeptical about many things in life at the cusp of the second millennium. Nonetheless, she traveled from Rhode Island to El Santuario de Chimayo in New Mexico to bring home a miracle for her dying father. Ultimately, Ann Hood discovered the courage to accept what had come her way, and an appreciation for the faith in miracles. Do Not Go Gentle is a profound journey into the nature of miracles, and one woman's revelatory reflection upon her spiritual heritage.
Keywords: Hood, Ann, -- 1956-; Catholic women -- United States -- Biography; Novelists, American -- 20th century -- Biography